Astaxanthin Protects Primary Hippocampal Neurons against Noxious Effects of Aβ-Oligomers. (1st March 2016) - Lobos, Pedro; Bruna, Barbara; Cordova, Alex; Barattini, Pablo; Galáz, Jose Luis; Adasme, Tatiana; Hidalgo, Cecilia; Muñoz, Pablo; Paula-Lima, Andrea
Abstract : Increased reactive oxygen species (ROS) generation and the ensuing oxidative stress contribute to Alzheimer's disease pathology. We reported previously that amyloid- β peptide oligomers (A β Os) produce aberrant Ca 2+ signals at sublethal concentrations and decrease the expression of type-2 ryanodine receptors (RyR2), which are crucial for hippocampal synaptic plasticity and memory. Here, we investigated whether the antioxidant agent astaxanthin (ATX) protects neurons from A β Os-induced excessive mitochondrial ROS generation, NFATc4 activation, and RyR2 mRNA downregulation. To determine mitochondrial H2 O2 production or NFATc4 nuclear translocation, neurons were transfected with plasmids coding for HyperMito or NFATc4-eGFP, respectively. Primary hippocampal cultures were incubated with 0.1  μ M ATX for 1.5 h prior to A β Os addition (500 nM). We found that incubation with ATX (≤10  μ M) for ≤24 h was nontoxic to neurons, evaluated by the live/dead assay. Preincubation with 0.1  μ M ATX also prevented the neuronal mitochondrial H2 O2 generation induced within minutes of A β Os addition. Longer exposures to A β Os (6 h) promoted NFATc4-eGFP nuclear translocation and decreased RyR2 mRNA levels, evaluated by detection of the eGFP-tagged fluorescent plasmid and qPCR, respectively. Preincubation with 0.1  μ M ATX prevented both effects. These results indicate that ATX protects neurons from the noxious effects of A β Os on mitochondrial ROS production, NFATc4 activation, and RyR2 gene expression downregulation.